REVIEW: POTENCY OF AMIDE DERIVATES AS CO-CRYSTAL FORMERS AND ITS IMPACT ON THE PHYSICOCHEMICAL OF ACTIVE PHARMACEUTICAL INGREDIENTS - Dina Apriani; Fikri Alatas (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Enhancing the physicochemical properties of active pharmaceutical ingredients (APIs) has been achieved by utilizing solid modification through the formation of co-crystals. Co-crystal was formed from active pharmaceutical ingredients and co-crystal former, more commonly called coformers. The occurrence of hydrogen bonds in the formation of co-crystals depends on the presence of groups that act as hydrogen bond donors or acceptors in API. Amide-derived coformers are widely used to form hydrogen bonds with API. This review aims to examine the potential of amide derivates as co-crystal-forming materials (coformers), groups in active pharmaceutical ingredients that can form hydrogen bonds with amide derivates and their impact on the physicochemical properties of API. Initial search results yielded 88 articles. Furthermore, the authors then conducted a screening based on exclusion and inclusion criteria, so that a total of 54 articles were obtained as review material. Data analysis in this journal review was carried out using descriptive analysis. Amide derivates have great potential to be used as co-crystal-forming materials due to the presence of amide or carboxamide groups (-CONH2), which can act as donors as well as acceptors of hydrogen bonds. Most of the amide-derived coformers with aliphatic amide groups, aromatic amides, pyridine carboxamides, and sulfonylcarboxamide form heterosynthon bonds with carboxylic groups on API. However, the formation of homosynthon bonds between amide and amide groups can occur, as in the 5-fluorouracil-urea co-crystal. Most of the amide derivates as coformers can change the physicochemical properties of APIs, especially in increasing the solubility and dissolution rate.